2004
DOI: 10.1161/01.atv.0000117180.57731.36
|View full text |Cite
|
Sign up to set email alerts
|

Human Evidence That the Cystatin C Gene Is Implicated in Focal Progression of Coronary Artery Disease

Abstract: Objective-Overexpression of elastolytic cysteine and aspartic proteases, known as cathepsins, is implicated in atherogenesis. The potential significance of imbalance in expression between cathepsins and their inhibitor cystatin C in cardiovascular disease has been highlighted by the demonstration of cystatin C deficiency in human atherosclerosis and abdominal aortic aneurysms. Methods and Results-We identified and characterized physiologically relevant polymorphisms in the promoter region of the cystatin C gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0
6

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 33 publications
5
74
0
6
Order By: Relevance
“…Even if non-renal influences, including polymorphisms in the promoter and exon 1 of the cystatin C gene [30,31], make cystatin C not completely reliable as a measure of renal function, most studies have found cystatin C to be a better marker of GFR than creatinine. In a recent meta-analysis [9], approximations of GFR performed with cystatin C compared with creatinine had higher correlation coefficients (0.816vs 0.742;P<0.001) and ROC-AUC (0.926 vs 0.837; P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Even if non-renal influences, including polymorphisms in the promoter and exon 1 of the cystatin C gene [30,31], make cystatin C not completely reliable as a measure of renal function, most studies have found cystatin C to be a better marker of GFR than creatinine. In a recent meta-analysis [9], approximations of GFR performed with cystatin C compared with creatinine had higher correlation coefficients (0.816vs 0.742;P<0.001) and ROC-AUC (0.926 vs 0.837; P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Apolipoprotein E (ApoE)-/-mice in which the CysC gene has been incapacitated (Cyst-/-) develop aneurysmal lesions and rupture of the limiting internal elastic lamina compared to ApoE-/-, Cystq/q mice (212,213). These studies on animal models are supported by occasional human genetic data (214,215). Patients with mutations in the CysC promoter gene have low circulating CysC concentrations (214,215).…”
Section: Future Perspectives For Cysc Applications Cysc As a Cardiovamentioning
confidence: 98%
“…Patients with mutations in the CysC promoter gene have low circulating CysC concentrations (214,215). The same mutations are associated with a higher number of coronary artery stenoses in a sub-group of patients (ns237) undergoing coronary angiography during an infarction, although they had no influence on the severity of the stenoses (214). These genotypes also do not influence patient survival at 3 years (215).…”
Section: Future Perspectives For Cysc Applications Cysc As a Cardiovamentioning
confidence: 99%
“…Its increased plasma concentrations have been found to predict the presence and severity of CVD in mild renal impairment, hence it could be an early marker of vascular risk (16). It has been suggested that cystatin C may directly contribute to atherogenesis by affecting arterial extracellular matrix remodeling (17).…”
Section: Uremic Retention Solutesmentioning
confidence: 99%